Development of Canva-Based E-book Story Learning (E-Boci) to Improve Indonesian Language Learning Outcomes in Elementary School - Shinta Permatasari; Arif Widagdo (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The low learning outcomes of the Indonesian language and the ability to think critically and argumentatively of elementary school students are problems that are still not handled optimally in learning practices. One of the factors causing this is the use of learning media that is less varied, not contextual, and has not utilized digital technology to the fullest. This study aims to develop and test the feasibility, practicality, and effectiveness of Canva-based E-Book Learning Stories (E-Boci) media as an innovative solution in improving Indonesian language learning outcomes in elementary schools. The method used is research and development (R&D) with the ADDIE model, which includes needs analysis, product design, expert validation, limited trials, and revision. Data were obtained through observation, interviews, documentation, as well as pretest and posttest of fourth-grade students in two elementary schools. The results showed that E-Boci was considered very feasible by material and media experts, practical in use by teachers and students, and effective in improving learning outcomes, especially in the aspects of critical thinking and the ability to formulate arguments. This media is proven to be able to encourage students' active involvement in learning and create more dialogic classroom interactions. This research provides theoretical contributions in the development of digital story-based media and practical contributions in providing teaching media that are innovative, accessible, and in accordance with the Merdeka Curriculum. E-Boci is recommended as an alternative learning medium that can be widely adapted in elementary schools.